PENGARUH GENDER, TEKANAN KETAATAN, TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGEMENT - Lidia Asnawanti, 13.05.52.0087; Setyowati, Widhy (Students Journal of Accounting and Banking, 2017)
Auditor is a profession that is one of its duties to audit the financial statements. Judgment audit has a significant influence on the final conclusion, so that it will affect the opinion that will be issued by the auditor. The objectives of the study were to find out gender, pressure of obedience, time budget pressure, task complexity and auditors experience on audit judgment. The data used is the primary data using questionnaires as instruments of data collection techniques distributed to the respondents. Respondents in this study are auditors working on KAP in Semarang. The number of questionnaires were distributed as many as 60 questionnaires, while those used as further analysis materials were 50 questionnaires. The results of this study indicate that gender variables have a significant negative effect on audit judgment. Variables of obedience pressure, task complexity and experience have a significant positive effect on audit judgment. For variable of time budget pressure have positive effect not significant to audit judgment.Keywords: Audit Judgement, Gender, Pressure of Obedience, Time Budget Pressure, Task Compilation, Experience